2020
DOI: 10.21203/rs.3.rs-106899/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptance and Completion of Rifapentine-Based TB Preventive Therapy (3HP) Among People Living with HIV (PLHIV) in Kampala, Uganda – Patient and health Worker Perspectives.

Abstract: BackgroundA 12-dose, once-weekly regimen of isoniazid and rifapentine (3HP) is effective in preventing tuberculosis (TB) among people living with HIV (PLHIV). We sought to identify potential barriers to and facilitators of 3HP implementation from the perspective of PLHIV and health workers in a routine HIV care setting in Kampala, Uganda.MethodsWe conducted semi-structured interviews with 25 PLHIV and 10 health workers at an HIV/AIDS clinic in Kampala, Uganda. For both groups, we explored their understanding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Various studies have reported on the significance of patient risk groups and residency as key determinants in treatment adherence (11,50,68,69). In our modeling, we equally found the two characteristics to be predictive of whether a patient will adhere to treatment or not.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Various studies have reported on the significance of patient risk groups and residency as key determinants in treatment adherence (11,50,68,69). In our modeling, we equally found the two characteristics to be predictive of whether a patient will adhere to treatment or not.…”
Section: Discussionsupporting
confidence: 60%
“…Further, we found out that some patients who were not residents of our study site catchment areas attended the health facilities located within Mukono. This could be because of the stigma associated with tuberculosis as was discussed by (69). In a similar scenario for covid-19 treatment seeking, a study by Muttamba et.…”
Section: Discussionmentioning
confidence: 85%